(untitled) (Physical Education, Health and Social Sciences, 2025)
Sindh has long been known as the land of Sufis, dervishes, and faqirs, where the philosophy of faqr emphasizes purifying the self and cultivating virtuous action. The region is rich with shrines and spiritual centers that have guided seekers of truth for generations. Among its eminent mystics, Budhal Faqir, born in 1865 near Shikarpur, stands out as a master of Sufi thought and practice. From an early age, he displayed a natural inclination toward the spiritual path, with a detached lifestyle and mystical temperament. He became a disciple of Pir Pagari Mian Hizbullah and adopted the Qadri Sufi order, showing no distinction of caste or religion. Beginning his poetry at fifteen, Budhal Faqir composed verses in moments of ecstasy, often while tending livestock or wandering in nature. He organized musical recitations at his shrine and mentored other Sufi singers, blending devotion with artistic expression. His poetry emphasizes universal love, the unity of existence, and spiritual ascent through fana (annihilation) and baqa (subsistence). Using simple language, allegorical characters, and local narratives, he conveyed mystical truths, divine love, self-purification, and union with God. His 178 published kafis reflect devotion, moral guidance, and spiritual insight, securing his place as a central figure in Sindhi Sufi literary heritage. Budhal Faqeer’s poetry delves into the profound concepts of Wahdat al-Wujud and Divine Love, exploring how these spiritual and ethical themes are expressed through his kafis. This study examines the artistic qualities and technical limitations of his poetry, focusing on how mystical concepts, prominent spiritual symbols, and allegorical elements are conveyed, while evaluating his contribution to Sindhi Sufi literary tradition. Using qualitative methods, the research analyzes the content and text of available kafis, compares Sufi doctrines, and reviews manuscripts, published collections, and historical references to highlight his poetic and spiritual significance. The findings establish Budhal Faqeer as a distinguished Sufi poet whose kafis embody fana, baqa, spiritual gnosis, and Divine Love. He conveys these concepts through allegorical characters, mystical metaphors, and symbolic motifs such as the alif, separation, and the Light of Truth. His poetry blends simplicity, classical tone, and mystical resonance, preserving the legacy of Sindhi Sufi literature. Keywords:Sufism, Wahdat al-Wujud, Divine Love, Kafis, Fana, Baqa, Symbol of Alif, Allegory.